Peritoneal Dialysis Cuff-Shaving—A Salvage Therapy for Refractory Exit-Site Infections. Issue 3 (May 2019) - Meng, Catarina; Beco, Ana; Oliveira, Ana; Pereira, Luciano; Pestana, Manuel
Introduction: Cuff-shaving has been described as a salvage technique for refractory exit-site infections, with conflicting data regarding infection and catheter outcomes. We describe our experience with cuff-shaving as a rescue therapy for exit-site infections unresponsive to systemic therapy. Methods: We retrospectively reviewed patients who underwent cuff-shaving between January 2012 and June 2017. Refractory exit-site infection was defined as purulent discharge from the exit site with no clinical response after 3 weeks of systemic antibiotic treatment. Results: Fifty-three cuff-shavings were included, mean age was 53.4 ± 13.4 years, 26 patients were male. Median dialysis vintage was 29 months (interquartile range [IQR] 14.3 – 38), and 39 (73.6%) were on continuous ambulatory peritoneal dialysis (CAPD). The exit-site infection rate before cuff-shaving was 1.12 episodes per patient-year and the median time from infection to shaving was 52 days (IQR 35 – 76). The most frequent agents were Staphylococcus aureus (34%), Corynebacterium spp. (17%) and Pseudomonas aeruginosa (15%). Median follow-up was 9 months (IQR 1 – 18.5), during which time 35 catheters were removed, 5 due to non-infectious reasons. Using the Kaplan-Meier survival analysis, median catheter survival was 24 months (95% confidence interval [CI] 4.17 – 43.83). At 12 months, the probability of catheter survival was 54% and was not statistically different between gram-positive and gram-negative agents, although it was significantly shorter for fungal agents. Conclusion: Cuff-shaving is a feasible rescue therapy to treat refractory exit-site infections. In our experience, it allowed resolution of infections in a significant proportion of cases, except for fungal agents, and therefore extended catheter survival time, besides being associated with a small rate of complications.